Accuracy and completeness of records of adverse events through interface terminology - González-Samartino, Maribel; Delgado-Hito, Pilar; Adamuz-Tomás, Jordi; Cano, Maria Fe Viso; Creus, Mònica Castellà; Juvé-Udina, María-Eulàlia (Revista da Escola de Enfermagem da USP, 2018)
Objective: To determine what adverse events, including pressure ulcers, infection of the surgical site and aspiration pneumonia, nurses record in clinical histories, in terms of diagnostic accuracy and completeness, through ATIC. Method: Observational, descriptive, cross-sectional, multicenter study of 64 medical-surgical and semi-critical units of two university hospitals in Catalonia, Spain, during 2015. The diagnostic accuracy was assessed by means of the correspondence between the event declared in the Minimum Basic Data Set and the problem documented by the nurse. The record was considered complete when it contained the risk of the event, prescriptions of care and a record of the evolution. Results: The sample evaluated included 459 records. The accuracy results of pressure ulcers are highly correlated between the nursing diagnosis recorded and that declared in the Minimum Basic Data Set. The accuracy in surgical site infection is moderate, and aspiration resulting in pneumonia is very low. The completeness of results is remarkable, except for the risk of bronchoaspiration. Conclusion: The adverse event recorded by nurses with greatest accuracy is pressure ulcers.